In vitro glycoengineering of a monoclonal antibody produced in insect cells - Zhurina, Anastasiia (2024)
Sugar modifications, in particular, N-glycans, largely determine protein quality, functionality, and, in case of therapeutic biomolecules, safety. Therapeutic monoclonal antibodies (mAbs) generate immune response through effector functions, for which they require complex N-glycans with high levels of galactose, sialic acids, and lack of core fucose, often unachievable in commercial production yielding suboptimal and heterogenous glycosylation pattern. Current glycoengineering strategies successfully tailor N-glycan composition on mAbs, yet fail to improve glycoprofile homogeneity. In this work, a recently developed cell-free in vitro glycoengineering approach was evaluated for generation of homogenous fully galactosylated N-glycoforms on therapeutic effector antibody Rituximab, characterized by low levels of galactose and glycan homogeneity in the originally marketed product. With an aim of targeting commercial mAbs, an industry-oriented protein production and glycoengineering strategy was designed on the basis of Lepidopteran insect cells. Rituximab was expressed in baculovirus-infected HighFive™ cells to obtain highly uniform starting N-glycoprofile, which was sequentially modified by recombinant human β-1,2 N-acetylglucosamintransferases I and II (MGAT1ΔTM and MGAT2ΔTM), and β-1,4-galactosyltransferase (GalTΔTM). The enzymatic cascade remodelled simple insect cell oligosaccharides on protein A-immobilized mAb species into complex human-like structures with a near 100% conversion rate. Recombinant enzyme production was tested in HighFive™ host, for which a functional expression protocol was developed, and a promising purification approach incorporating solubilizers was proposed. Production of Rituximab in HighFive™ cells was challenged by poor mAb assembly despite optimization of cell culture conditions. The results indicated a need for significant effort in improving insect cell-based protein production strategy to achieve higher enzyme and antibody yields. With suggested directions for further research, assessed in vitro glycoengineering platform can become an effective toolbox for generating high-efficacy therapeutic mAbs in industrial settings.